More than Just a Simple Cardiac Envelope; Cellular Contributions of the Epicardium - Dueñas, Angel; Aranega, Amelia E.; Franco, Diego (Frontiers in Cell and Developmental Biology, 2017)
The adult pumping heart is formed by distinct tissue layers. From inside to outside, the heart is composed by an internal endothelial layer, dubbed the endocardium, a thick myocardial component which supports the pumping capacity of the heart and exteriorly covered by a thin mesothelial layer named the epicardium. Cardiac insults such as coronary artery obstruction lead to ischemia and thus to an irreversible damage of the myocardial layer, provoking in many cases heart failure and death. Thus, searching for new pathways to regenerate the myocardium is an urgent biomedical need. Interestingly, the capacity of heart regeneration is present in other species, ranging from fishes to neonatal mammals. In this context, several lines of evidences demonstrated a key regulatory role for the epicardial layer. In this manuscript, we provide a state-of-the-art review on the developmental process leading to the formation of the epicardium, the distinct pathways controlling epicardial precursor cell specification and determination and current evidences on the regenerative potential of the epicardium to heal the injured heart.